ASSESSMENT OF REPRODUCTIVE DISORDER REMEDIAL PRACTICE (RDRPA) ADOPTION BY DAIRY FARMERS IN UNDULATING PLAIN REGION OF PUNJAB - KASRIJA, R; VERMA, H K; GANDOTRA, V K (The Indian Journal of Animal Reproduction, 2016)
A study was conducted in the undulating plain region of Punjab to assess the reproductive disorder remedialpractice adoption (RDRPA) level of dairy farmers possessing small (1-9 animal), medium (10-30 animal) and large(>30 animal) dairy units. There was significant difference (p
Keywords: Dairy; Disorder; Punjab; Remedial practice; Reproduction